Application of organic azides for the synthesis of nitrogen-containing molecules - Chiba, Shunsuke (2013)
In this account, recent advances made on the reactions of several types of organic azides, such as vinyl azides, cyclic 2-azido alcohols, a-azido carbonyl compounds, towards the synthesis of nitrogen-containing molecules are described.